Freight trains are back and they're on a roll. - Ola, Per; d'Aulaire, Emily (Smithsonian)
Asserts that the United States rail freight industry is booming as more goods than ever now travel by rail. Union Pacific, Santa Fe and other rail freight handlers with more than $1 billion in annual revenues; How truck trailers are being transported by rail; History of railroading in the US; Staggers Rail Act of 1980; Gwen Boren, dispatcher at the Harriman Dispatching Center in Omaha, Nebraska; FRED (Flashing Rear End Device); Rail buffs.